Preparation, characterization and in vitro bioactivity evaluation of quercetin and syringic acid loaded colloidal nanoparticles of chitosan-caseinate complex - Aref Moradi Kolamaki; Maryam Mohadjerani (Carbohydrate Polymer Technologies and Applications, 2025)
Quercetin (Qu) and syringic acid (SA) possess significant biological properties but suffer from low bioavailability. Encapsulation within biopolymer matrices provide a promising solution to this challenge. Polyelectrolyte nanoparticles were formed by caseinate and chitosan. This innovative approach improves the bioavailability of these metabolites while enabling controlled release and targeted delivery, addressing key challenges in drug delivery systems. Qu-SA-loaded chitosan-caseinate nanoparticles were successfully prepared with a particle yield of 72.4 %. The measured loading efficiency and capacity were estimated at 76.1 and 40.3 % for quercetin, and 62.4 and 22.7 % for syringic acid, respectively. The Qu-SA-loaded nanoparticles exhibited a quasi-spherical shape with a non-aggregated morphology, as confirmed by SEM, TEM, and AFM analyses. These nanoparticles were stable, with an appropriate dispersion of 0.0463 and a surface charge of +46.2. Release studies after 20 h showed that syringic acid exhibited a release of 66.5 %, whereas quercetin reached 41.7 %. The nanoparticles demonstrated significant antioxidant activity, as evidenced by IC50 value of 12.5 µg/mL for DPPH radical scavenging potential. These findings suggest that chitosan-caseinate nanoparticles are effective carriers for enhancing the delivery and bioactivity of syringic acid and quercetin, offering potential applications in functional foods, pharmaceuticals goods, and dietary supplements.